Spatial Three Degree of Freedom Parallel Manipulator Forward Kinematic Position Analysis - Rao Pundru, Srinivasa; Rao Nallur, Mohan (International Journal of Engineering and Technology, 2018)
This work presents forward kinematic position analysis of a spatial three degree of freedom parallel manipulator, which has three symmetric loops. The three loops consist of an actuated sliding links- rotational and spherical joints. The actuated sliding links are attached to inclined base platform via rotational joints. The limbs are connected from rotational joints to moving platform by spherical joints. The degree of freedom of a spatial parallel manipulator is analyzed via kutzbach criterion. The forward kinematic position analysis carried out by using 3-coupled trigonometric equations which are formulated with side and behaviour constraints of the manipulator. There are many difficulties in solving the system of non-linear equations in kinematics of manipulator therefore by using MATLAB the three non-linear coupled algebraic equations are solved. The forward position kinematic analysis part is used in the development procedure of spatial parallel manipulator to check, the required and obtained positions of the moving platform of the developed manipulator.Â Â